PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK BENGKEL RESMI TERHADAP NILAI PELANGGAN SERTA IMPLIKASINYA PADA KEPUASAN PELANGGAN (SUATU SURVEY PADA PELANGGAN BENGKEL RESMI KENDARAAN MPV DI BAWAH 2500 CC DI KOTA BANDUNG) - Wardhana, Aditya (JURNAL KEBANGSAAN, 2013)
This research aims to obtain empirical evidence regarding the influence of the quality of service and the brand image of the customers as well as its implications on customer satisfaction workshop ATPM official vehicle MPV under 2500 cc in Bandung. The results of this research are expected to contribute in the development of management science in particular management of marketing and consumer behavior. For the workshop as well as a type of ATPM official practitioners, expected results of this research can provide useful information about the importance of service quality, brand image, customer value, in an effort to increase customer satisfaction. Research conducted on the official workshop ATPM vehicle MPV under 2500 cc in the city of Bandung by as much as 22 official car dealers workshop from 5 ATPM. A population study of 14.947 respondents and of the population of 375 people respondents as samples. This method uses a quantitative approach with survey methods. While his research is descriptive research tipa and verificative explanatory research with a time horizon to its data in the form of cross-sectional that reflects the image of a State at any given moment. To test the hypothesis of research statistical methods used path analysis (path analysis).The test results found no significant relationship between service quality and brand image official workshop, in addition to that of the test results found no significant influence between the service quality and brand image of good customers and partially simultaneous, also found significant effects between the value customers with customer satisfaction.